Visual assessment and diagnosis of a timber railway station warehouse in Foz do Tua - Sousa, Hélder S. (2017)
Aiming at the rehabilitation of a timber warehouse in the Tua train station for a new use, it was necessary to assess the level of conservation of the building’s elements and determine whether intervention measures were required. This work summarizes the assessment made of the timber elements by means visual inspection and non-destructive testing. The main results, obtained in the diagnostic survey, were the conservation level of the timber warehouse, the visual strength grading of the timber elements and damage maps indicating the main pathologies and its probable causes.